A relação entre consciência fonológica e aquisição da escrita em crianças do 1º ano do ensino fundamental, antes e após um programa de intervenção - Santana, Thayane Sampaio Campos (2018)
The present study investigates the relationship between writting and phonological awareness before and after applying an intervention program in ten 6-7 year-old children,, from 1st year of Elementary School (Key stage 1 Year 1), from the same classroom of a private midsize School, located in the peripheral l zone of Feira de Santana city, Bahia state, Brazil. Phonological awareness is understood to be the ability to reflect and manipulate speech sounds, at the syllable and phoneme levels. The written was analyzed according to proposed written stages by Ferreiro and Teberosky (1998) and the misspelling was evaluated according Cagliari (1997). Phonological awareness was evaluated using the “CONFIAS test – Sequential Evaluated Instrument of Phonological awareness” proposed by Moojen et alii (2014). The intervention program is a CONFIAS adaptation suggested by Cardoso and Capellini (2009). The goal of this research is to describe the student performance in an isolated word dictation; to analyse the performance in CF tasks; to identify used strategies from subjects in the CF tests; to compare the results before and after the intervention program application; to verify whether there is some relationship between the results of CF tests and misspelling. As theoretical contribution, mainly, the manuscripts were used by Cagliari (1997), Ferreiro and Teberosky (1998), Morais (2000), Moreira (2013), Moojen et alii (2014) and Pepe (2014). The results found even though they were literate, children still had difficulties performing the task of phonemic segmentation; the intervention contributed, above all, to the performance of the subjects in the tasks at the phonemic level; the tasks involving rhyme and segmentation of phonemes are the most complex to perform; the children use strategies in trying to achieve the CF tasks; errors of two natures were found in the word dictation data: misuse of letters and modification of the segmental structure. This research contributes tor the medical and education fields, considering that it can help rehabilitation practices from patients with language disorders or learning difficulties, especially those related to writing, to understanding the difficulties associated with phonological awareness; besides offering subsidies to teachers that work with literacy classes